High-energy micro-forging and ion nitriding composite surface strengthening and toughening method for large die
Through the high-energy micro forging and ionic nitriding composite surface strength and toughening methods, the problems of insufficient toughness and surface integrity of large mold materials are solved, and the effects of improving surface quality, improving fatigue performance and extending service life are achieved.
Patent Information
- Application Number
- CN202411598945.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing technology has shortcomings in the toughness and surface integrity of large mold materials. The traditional strengthening method has a long processing time, high energy consumption, environmental pollution and high cost, making it difficult to meet the high performance needs of large molds.
Using high-energy micro forging and ionic nitriding composite surface toughening methods, a cold hardened layer and plastic deformation are formed through traditional shot peening pretreatment, and then a nitriding layer is formed in the ionic nitriding equipment, and a high-energy micro forging technology is used to make nitrogen. The layer is compacted to form a surface nanostructure.
It significantly improves the surface quality of large molds, reduces surface roughness, enhances material wear resistance, improves fatigue performance by more than 40%, extends the service life of the mold, and reduces costs.
Smart Images

Figure CN119465017A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of mold surface treatment, and particularly relates to a high-energy micro-forging and ion nitriding composite surface toughening method for a large mold. Background Art
[0002] Large molds play a vital role in industrial production. Their lifespan reflects the technical level of the mold industry and affects production efficiency and cost. With the rapid development of my country's aerospace and other national strategic demand fields, the demand for large-scale, integrated, and precise high-performance key components is increasing. For example, landmark projects such as fighter jets and large aircraft require giant forging dies, which are extremely difficult to manufacture using traditional methods. In addition, the mold working environment is harsh and is often affected by various factors such as high temperature, high pressure, wear and corrosion. Forging dies manufactured using traditional methods have poor performance and extremely low service life. Therefore, it is particularly important to develop an efficient, environmentally friendly, and energy-saving surface strengthening method.
[0003] Common surface strengthening methods such as carburizing and nitriding, although they improve the surface performance of the mold to a certain extent, have problems such as long processing time, high energy consumption, and environmental pollution. Traditional shot peening strengthening technology uses a larger diameter of projectiles, which will increase the roughness of the mold surface, cause more stress concentration points, increase crack sources, and reduce the surface strengthening performance of shot peening. New strengthening methods, such as high-pressure water jet shot peening, ultrasonic shot peening, and composite shot peening, are costly and complex to operate. For example, Chinese Patent 202410682210.7 provides a surface strengthening method of composite ultrafast laser shock strengthening and salt bath soft nitriding, which is more suitable for fine operation of small molds. It is complicated to operate on large molds, the cost is high, and it will cause problems such as surface thermal damage. For example, Chinese Patent 202010887214.0 provides a composite shot peening strengthening method for leaf springs, which combines coarse shot peening with microparticle shot peening. Although it achieves the effect of reducing surface roughness, the surface quality improvement effect is limited. Therefore, developing a surface strengthening method for large molds is of great significance for improving the performance of molds and simplifying the strengthening process.
[0004] Ion nitriding technology is fast, has little deformation, is environmentally friendly and efficient, and is widely used in the field of mold surface strengthening. The resulting nitrided layer has excellent mechanical properties, such as high hardness, high wear resistance, good toughness and fatigue strength. Compared with microparticle shot peening, the projectile density used in high-energy micro-forging technology is about twice that of its projectile density, and the speed is more than twice that of its projectile speed, and the particle energy is greater. On the basis of improving the surface hardness and residual stress, the surface roughness is reduced, and the surface integrity and wear resistance of the mold surface are improved. The impact of high-speed projectiles forms defects such as dislocations and twins on the surface of the material, which gradually accumulate to obtain a surface nanostructure and improve the toughness of the mold.
[0005] If the above-mentioned ion nitriding and high-energy micro-forging processes are combined, it can not only improve the surface hardness of the material, but also improve the surface roughness and toughness, thereby achieving the purpose of improving the surface quality of large molds. Summary of the invention
[0006] In view of the shortcomings of existing strengthening methods in terms of toughness and surface integrity of large mold materials, the present invention provides a high-energy micro-forging and ion nitriding composite surface toughening method for large molds, which can improve the surface performance of the material while reducing its surface roughness, improving the toughness of the material and extending its service life. The large mold surface obtained by this technology is smooth, the material's wear resistance is enhanced, the friction coefficient is reduced, and the fatigue performance is improved by more than 40%.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A high-energy micro-forging and ion nitriding composite surface toughening method for a large mold comprises the following steps:
[0009] S1. Clean large molds;
[0010] S2. Use the traditional shot peening method to perform rough shot peening on the cleaned large mold;
[0011] S3, cleaning and drying the mold after conventional shot peening;
[0012] S4, placing the cleaned and dried mold in an ion nitriding device for nitriding treatment;
[0013] S5. Use high-energy micro-forging technology to strengthen the surface of the mold after ion nitriding;
[0014] S6. Polish, clean, dry and oil the mold after high-energy micro-forging treatment.
[0015] Preferably, in step S1, the large mold is made of mold steel, has a size of more than 600 mm, and a hardness of 38-55 HRC.
[0016] Preferably, in step S1, the large mold is cleaned, specifically: the large mold is mechanically ground using sandpaper with a mesh size of 180-3000, then cleaned using ethanol, and then dried using compressed air.
[0017] Preferably, in step S2, the technical parameters of the conventional shot peening method include: a shot diameter of 0.4-0.8 mm, a shot peening speed of 30-80 m / s, a shot hardness of 400-700 HV, and a shot density of 6-8 g / cm 3 .
[0018] Preferably, in step S3, the mold after the conventional shot peening treatment is cleaned and dried, specifically: after cleaning with ethanol, it is dried with compressed air.
[0019] Preferably, in step S4, the technical parameters of ion nitriding treatment of the large mold include: ion nitriding is performed in a pulse plasma furnace, the working voltage is 400-800 V, the working current is 60-120 A, the frequency is 3-12 kHz, the duty cycle is 40%-80%, the temperature is 450-550°C, and the nitriding time is 4-10 hours. After the ion nitriding treatment is completed, the nitrided sample is cooled to room temperature under vacuum conditions.
[0020] Preferably, in step S5, the high-energy micro-forging technology is specifically a process of accelerating the special micro-beads to a speed higher than that of conventional shot peening by using high-pressure airflow, and forging the working surface of the component at a suitable angle. Compared with the existing micro-particle shot peening technology, the special micro-beads used in the high-energy micro-forging of the present invention have a higher speed and density, and can produce a better surface strengthening effect.
[0021] Preferably, in step S5, the technical parameters of the high-energy micro-forging technology include: the material of the special micro-beads is an alloy material, such as high-speed steel, with a hardness of more than 1400 HV and a density of 15 g / cm 3 Above, the diameter is 50~100μm, and the speed of special microbeads is 150~260 m / s.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The surface strengthening method provided by the present invention uses traditional shot peening pretreatment to induce a uniform and dense cold-work hardening layer and plastic deformation on the mold surface. The grain boundaries produced by the plastic deformation serve as channels for nitrogen atoms to enter the interior of the large mold. The nitrogen atoms react chemically with the workpiece material to form a hard surface hard strengthening layer. Then, high-energy micro-forging technology is used to densify the nitrided layer, and at the same time, a large number of dislocations, twins, etc. are rapidly accumulated on the surface of the large mold to form a surface nanostructure, thereby achieving the purpose of surface toughening. This method integrates the advantages of the above-mentioned various processes, reduces surface roughness, effectively improves the surface quality of large molds, improves the friction and wear performance and fatigue resistance of large molds, and increases the surface hardness while maintaining the toughness of the material.
[0024] This method effectively improves the surface quality of large molds. The surface of the mold after treatment is smoother, the surface roughness is reduced, and the stress concentration is reduced; the surface residual compressive stress is increased, a larger residual compressive stress layer is formed, crack propagation is inhibited, and fatigue strength and wear resistance are improved; the surface toughness of large molds is improved by micro-nano-scaling of the surface structure, and the occurrence of microcracks is reduced; the tiny micro-pits on the surface can form a lubricating film to enhance the sliding performance; the fatigue life of large molds is extended by more than 40%, which greatly increases the number of times they are used and reduces costs. This method is suitable for larger molds, is simple to operate, and is economical and convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 It is a flow chart of a high-energy micro-forging and ion nitriding composite surface toughening method for a large mold of the present invention;
[0027] Figure 2 This is a comparison diagram of the mold surface without strengthening and after composite strengthening treatment in Example 1 of the present invention. Figure 2 (a) is the untreated specimen, and (b) is the composite strengthening treated specimen. DETAILED DESCRIPTION
[0028] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0029] like Figure 1 As shown, a high-energy micro-forging and ion nitriding composite surface toughening method for a large mold includes the following steps:
[0030] S1. Clean large molds;
[0031] S2. Use the traditional shot peening method to perform rough shot peening on the cleaned large mold;
[0032] S3, cleaning and drying the mold after conventional shot peening;
[0033] S4, placing the cleaned and dried mold in an ion nitriding device for nitriding treatment;
[0034] S5. Use high-energy micro-forging technology to strengthen the surface of the mold after ion nitriding;
[0035] S6. Polish, clean, dry and oil the mold after high-energy micro-forging treatment.
[0036] The surface strengthening method provided by the present invention uses traditional shot peening pretreatment to induce a uniform and dense cold-work hardening layer and plastic deformation on the mold surface, and uses the grain boundaries generated by the plastic deformation as a channel for nitrogen atoms to enter the interior of the large mold. The nitrogen atoms react chemically with the workpiece material to form a hard surface hard strengthening layer. Then, high-energy micro-forging technology is used to densify the nitrided layer, and at the same time, a large number of dislocations, twins, etc. are rapidly accumulated on the surface of the large mold to form a surface nanostructure, thereby achieving the purpose of surface toughening. The surface quality of the large mold is greatly improved and the service life is extended.
[0037] In one embodiment of the present invention, in step S1, the large mold is made of mold steel, has a size of more than 600 mm, and a hardness of 38-55 HRC.
[0038] In one embodiment of the present invention, in step S1, the large mold is cleaned, specifically: the large mold is mechanically ground using 180-3000 mesh sandpaper, then cleaned with ethanol, and then dried with compressed air.
[0039] In one embodiment of the present invention, in step S2, the technical parameters of the conventional shot peening method include: a shot diameter of 0.4-0.8 mm, a shot peening speed of 30-80 m / s, a shot hardness of 400-700 HV, and a shot density of 6-8 g / cm 3 Furthermore, the hardness of the projectile is about 500 HV and the density is 7 g / cm 3 The present invention uses steel shot with a larger diameter to pre-peen the surface of a large mold to remove burrs, scale, oil stains and other undesirable substances on the surface of the parts and improve the surface quality. A cold-work hardening layer is formed and plastic deformation occurs, which acts as an ion short-circuit diffusion channel to promote the diffusion of nitrogen ions into the interior of the large mold, thereby improving the hardness and wear resistance of the parts.
[0040] In one embodiment of the present invention, in step S3, the mold after the conventional shot peening treatment is cleaned and dried, specifically: after cleaning with ethanol, it is dried with compressed air.
[0041] In one embodiment of the present invention, in step S4, the cleaned large mold is placed in a pulse plasma furnace, and the workpiece is nitrided in a vacuum environment using the glow discharge phenomenon. In a nitrogen-containing atmosphere (such as ammonia) below normal pressure, a glow discharge phenomenon is generated by applying a DC voltage of hundreds of volts between the furnace body (anode) and the workpiece (cathode). Ammonia molecules are ionized into active nitrogen atoms and hydrogen atoms, and when the gas is ionized, plasma is formed, thereby generating high-energy nitrogen ions. These active nitrogen atoms gain speed under the action of the electric field and bombard the surface of the workpiece at high speed. During the bombardment process, some iron atoms are sputtered out and combined with nitrogen to form FeN, while some nitrogen atoms are adsorbed to the surface of the workpiece. The nitrogen atoms adsorbed on the surface of the workpiece migrate to the inside of the workpiece through a diffusion mechanism to form a nitride layer. This process includes the deposition of nitrogen atoms and subsequent volume diffusion, and finally forms a dense and hard nitride layer on the surface of the workpiece.
[0042] In one embodiment of the present invention, the technical parameters for ion nitriding treatment of the large mold include: ion nitriding is performed in a pulse plasma furnace, the working voltage is 400-800 V, the working current is 60-120 A, the frequency is 3-12 kHz, the duty cycle is 40%-80%, the temperature is 450-550°C, and the nitriding time is 4-10 hours. After the ion nitriding treatment is completed, the nitrided sample is cooled to room temperature under vacuum conditions.
[0043] In one embodiment of the present invention, in step S5, the high-energy micro-forging technology is specifically a process of using high-pressure airflow to accelerate special micro-beads to a speed higher than that of traditional shot peening, and forging the working surface of the component at a suitable angle. The micro-forging processing speed can reach 1m / min, and the appropriate processing speed and strengthening channel are selected to ensure that the micro-beads evenly and completely strengthen the entire working surface.
[0044] Compared with the existing micro-particle shot peening technology, the special micro-beads used in the high-energy micro-forging of the present invention have a higher speed and density, and can produce better surface strengthening effects. The micro-beads selected for high-energy micro-forging are very small in size, belonging to the micron level, and have little effect on surface roughness during the strengthening process, thereby improving the surface quality. The shot peening has a high density and a high speed, and the impact energy formed is very large, which densifies the nitride layer. Under the impact of high energy, the surface of the material rapidly undergoes plastic deformation, forming surface substructures such as dislocations and twins, and achieving surface nano-ization. Therefore, while improving the surface hardness and surface residual stress, the high-energy micro-forging technology ensures the surface integrity and material toughness of the material, and realizes surface toughening treatment.
[0045] The surface of large molds treated by traditional shot peening has short-circuit diffusion channels formed through grain boundaries, subgrain boundaries, dislocations, etc., which is conducive to the diffusion of nitrogen atoms adsorbed on the surface of the workpiece into the interior of the workpiece to form a deeper nitride layer. High-energy micro-forging densifies the nitride layer and reduces the surface roughness, thereby achieving the effect of improving the surface hardness, wear resistance and corrosion resistance of the material.
[0046] Preferably, in step S5, the technical parameters of the high-energy micro-forging technology include: the material of the special micro-beads is an alloy material, such as high-speed steel, with a hardness of more than 1400 HV and a density of 15 g / cm 3 Above, the diameter is 50~100μm, and the speed of special microbeads is 150~260 m / s.
[0047] In one embodiment of the present invention, in step S6, the large mold after composite strengthening is polished, cleaned, dried and oiled. The oiling treatment can further form a black oxide film on the surface of the large mold, improve its anti-oxidation performance, and at the same time obtain satisfactory hardenability and hardenability, prevent cracking and reduce deformation.
[0048] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the specific embodiments of the present invention are described in detail below. The above-mentioned composite strengthening method is used to perform composite strengthening treatment on the surfaces of different mold steel samples. The specific operation is as follows:
[0049] Example 1
[0050] The steel specimen to be strengthened was made of die steel 5CrNiMo, with a thickness of 10 mm and an area to be strengthened of 100 mm × 100 mm;
[0051] S1: After grinding with a flat wheel machine, use 1000-grit sandpaper for mechanical grinding, and use a cloth soaked in ethanol to thoroughly clean the mold surface. Use an air compressor to provide dry, oil-free compressed air, and use a compressed air nozzle to dry the mold steel surface.
[0052] S2: The die steel sample was fixed on the working platform of the compression shot peening machine, with a diameter of 0.6 mm, a shot peening speed of 80 m / s, a hardness of about 500 HV, and a density of 7 g / cm 3 The S110 alloy shots on the left and right were subjected to conventional shot peening, and the number of impacts was 1.
[0053] S3: For the mold steel specimen after conventional shot peening, the mold surface was thoroughly cleaned with a cloth soaked in ethanol and dried with compressed air;
[0054] S4: The cleaned and dried steel sample was placed in a pulse plasma furnace for ion nitriding treatment, with an operating voltage of 700 V, an operating current of 100 A, a frequency of 10 kHz, a duty cycle of 60%, an environment of φ ( N ): φ ( H ) = 1:3, a temperature of 500 °C, and nitriding for 10 h. Subsequently, the nitrided sample was cooled to room temperature under vacuum conditions.
[0055] S5: The nitrided die steel sample was fixed on the working platform of the high-energy micro-forging equipment, using a shot with a diameter of 100 μm, a projectile speed of 200 m / s, a hardness of 1400 HV, and a density of 15 g / cm 3 The YG6A alloy projectiles on the left and right were subjected to high-energy micro-forging treatment, and the number of impacts was 1.
[0056] S6: Die steel specimen after the polishing, cleaning and drying composite treatment.
[0057] Example 2
[0058] The steel specimen to be strengthened is made of die steel 4Cr5MoSiV1, with a thickness of 10 mm and an area to be strengthened of 100 mm × 100 mm;
[0059] The specific operation is the same as that of Example 1.
[0060] Comparative Example 1 (Traditional shot peening)
[0061] The steel specimen to be strengthened is made of die steel 5CrNiMo, with a thickness of 10 mm and an area to be strengthened of 100 mm × 100 mm;
[0062] S1: After grinding with a flat wheel machine, use 1000-grit sandpaper for mechanical grinding, and use a cloth soaked in ethanol to thoroughly clean the mold surface. Use an air compressor to provide dry, oil-free compressed air, and use a compressed air nozzle to dry the mold steel surface.
[0063] S2: The die steel sample was fixed on the working platform of the compression shot peening machine, with a diameter of 0.6 mm, a shot peening speed of 80 m / s, a hardness of about 500 HV, and a density of 7 g / cm 3 The S110 alloy shots on the left and right were subjected to conventional shot peening, and the number of impacts was 1.
[0064] S3: Polished, cleaned and dried die steel specimen after conventional shot peening.
[0065] Comparative Example 2: (Traditional shot peening)
[0066] The steel specimen to be strengthened is made of die steel 4Cr5MoSiV1, with a thickness of 10 mm and an area to be strengthened of 100 mm × 100 mm;
[0067] The specific operation is the same as that of Example 3.
[0068] The above-mentioned embodiment was subjected to surface strengthening, and the hardness and surface residual compressive stress of the mold steel sample were measured. The results are shown in Table 1:
[0069] Table 1 Hardness and residual compressive stress measurement of various mold steel samples before and after traditional shot peening and composite treatment
[0070]
[0071] As shown in Table 1, after the composite strengthening treatment of the present invention, the residual compressive stress on the surface of the mold sample can reach above -900 MPA, which is significantly improved compared with the residual compressive stress value in the prior art. The metal surface hardness can be increased by about 3 to 9 HRC. Figure 2 (a) is the surface morphology of the untreated specimen, the surface grains are relatively coarse, the grain boundaries are clearly visible, and there is no influence of plastic deformation. Figure 2 As shown in (b), after high-energy micro-forging and ion nitriding composite surface strengthening treatment, the mold steel has a dense nitrided layer, diffusion layer and matrix from the outside to the inside, and there is a surface nano-crystallization phenomenon. At the same time, the surface roughness of the mold steel can be reduced to the mirror processing level (Ra<0.04 μm) / grinding processing level (Ra<0.8 μm). The surface quality of large molds is greatly improved, the surface hardness is increased while maintaining the toughness of the material, and the friction and wear performance and fatigue resistance of large molds are effectively improved, which increases the mold life by more than 40%, and this method has the advantages of high efficiency and low cost.
[0072] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A high-energy micro-forging and ion nitriding composite surface toughening method for large molds, characterized in that: The following steps are involved: S1. Clean large molds; S2. Use the traditional shot peening method to perform rough shot peening on the cleaned large mold; S3, cleaning and drying the mold after conventional shot peening; S4, placing the cleaned and dried mold in an ion nitriding device for nitriding treatment; S5. Use high-energy micro-forging technology to strengthen the surface of the mold after ion nitriding; S6. Polish, clean, dry and oil the mold after high-energy micro-forging treatment.
2. The high-energy micro-forging and ion nitriding composite surface toughening method for large molds according to claim 1 is characterized in that: In step S1, the large mold is made of mold steel, has a size of more than 600 mm, and a hardness of 38-55 HRC.
3. The high-energy micro-forging and ion nitriding composite surface toughening method for large molds according to claim 1 is characterized in that: In step S1, the large mold is cleaned, specifically, the large mold is mechanically ground using sandpaper with a mesh size of 180-3000, then cleaned using ethanol, and then dried using compressed air.
4. The high-energy micro-forging and ion nitriding composite surface toughening method for large molds according to claim 1, characterized in that: In step S2, the technical parameters of the conventional shot peening method include: shot diameter of 0.4-0.8 mm, shot peening speed of 30-80 m / s, shot hardness of 400-700 HV, shot density of 6-8 g / cm 3 .
5. The high-energy micro-forging and ion nitriding composite surface toughening method for large molds according to claim 1, characterized in that: In step S3, the mold after the conventional shot peening treatment is cleaned and dried, specifically: after cleaning with ethanol, it is dried with compressed air.
6. The high-energy micro-forging and ion nitriding composite surface toughening method for large molds according to claim 1, characterized in that: In step S4, the technical parameters of ion nitriding treatment of the large mold include: ion nitriding is carried out in a pulse plasma furnace, the working voltage is 400~800 V, the working current is 60~120 A, the frequency is 3~12 kHz, the duty cycle is 40%~80%, the temperature is 450~550°C, and the nitriding time is 4~10h.
7. The high-energy micro-forging and ion nitriding composite surface toughening method for large molds according to claim 1, characterized in that: In step S5, the technical parameters of the high-energy micro-forging technology include: the material of the special micro-beads is an alloy material with a hardness of more than 1400 HV and a density of 15 g / cm 3 Above, the diameter is 50~100μm, and the speed of special microbeads is 150~260 m / s.
Citation Information
Patent Citations
Steel plate spring composite shot blasting strengthening method
CN112011674A
Surface strengthening method combining ultrafast laser shock strengthening and salt bath tufftriding
CN118563083A